Zorganizowane wyjazdy na wieś jako forma pomocy dzieciom łódzkim w latach I wojny światowej - Stawiszyńska, Aneta (Zeszyty Wiejskie, 2019)
Horrors of the First World War affected the life of all citizens of Lodz, especially the young ones. Victualing-related problems led to a phenomenon of hunger and numerous strictly connected diseases. Various charity organizations tried to help children from Lodz, for example by organizing countryside excursions for them. The children took part both in a few-week summer stays, as well as in a few-month visits to the countryside. One of the main aims set by the organizers was to improve the overall well-being of children by providing them with proper nutrition. Even though the children staying in the countryside were required to work and help farmers, some positive influence of the aforementioned stays was frequently indicated.